PERAN HUMAS DALAM KAMPANYE PENCEGAHAN NARKOTIKA MELALUI INSTAGRAM BADAN NARKOTIKA NASIONAL KABUPATEN SUKABUMI - Khayla Zahwa Annisa; Willy Bachtiar (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
Drug abuse remains a serious problem in Indonesia, especially among adolescents and young adults, making effective prevention strategies necessary. This study aims to understand the role of Public Relations unit of BNNK Sukabumi in designing and implementing drug prevention campaigns through Instagram. The research method uses a descriptive qualitative approach, with data collected through participant observation, interviews, and literature study. The results show that the Public Relations unit of BNNK Sukabumi has carried out strategic messages in accordance with the Excellence in Public Relations model. The PR unit does not only disseminate information, but also designs content, maintains ethics and social responsibility, and builds two-way communication with the public through Instagram.